PANDANGAN IMAN KRISTEN MENGENAI BUNUH DIRI - Adriani Adriani; Titania Modingge; Voni Yanti Rante Limbong; Hendriani Teti Mattu; Penina Penina (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This research aims to explore and analyze the Christian faith's perspectives on the phenomenon of suicide. This phenomenon is a complex and sensitive issue, considering the moral and spiritual values that underlie Christian beliefs. The study employs a qualitative approach, gathering and analyzing data from various Christian theological sources, including the Bible, prominent theological works, and church documents. The results of the study indicate that the Christian faith's view on suicide is closely tied to the belief in life as a divine gift from God. Human existence is regarded as a manifestation of the divine plan, hence ending one's life is questioned from an ethical perspective. However, the research also finds complexities in the interpretation of biblical texts and the development of theology over time. Additionally, the study highlights perspectives on extreme psychological conditions and unbearable suffering as factors influencing the Christian understanding of suicide. Some theologians consider extreme cases with empathy, emphasizing compassion and social support as the church's response to profound suffering. The research also notes that hope in the ultimate resurrection is a crucial element in the Christian perspective on suicide. Belief in life after death shapes the outlook on choices between life and death in this world. This research provides in-depth insights into the Christian faith's views on suicide, recognizing diverse interpretations among Christian theologians. The findings of this study are expected to contribute to broader ethical and theological discussions on this issue, as well as assist in forming a sensitive and attentive pastoral approach in supporting individuals facing mental and emotional crises.